Dukungan Sosial Terhadap Pemanfaatan Posbindu pada Lansia di Mekarsari, Cimanggis Tahun 2019 - A. Heri Iswanto; Marina Ery Setyawati; Rahmah Hida Nurrizka; Mawaddah Elbaking (Kampurui Jurnal Kesehatan Masyarakat, 2020)
Elderly’s posbindu is a community-based health that provides health services for the elderly. The increasing of elderly population in Indonesia indicates that posbindu should have a certain quality service. But in its utilization, some elderly did not use it well. This study aims to examine the differences in social support for the posbindu utilization between case and control group of the elderly in Mekarsari, Cimanggis. This study was used a case control design. The population in this study are elderly who visited posbindu in Mekarsari at least 1x during January-April 2019. The sample size was 34 people with a case:control rasio of 1:1. The sampling technique used is simple random sampling by giving random numbers to each individual who included the inclusion criteria. Data collection by interview method using questionnaire instrument. The result showed that there was no difference social support between case and control group. This is due to the Sig. of informational support (0,576), emotional support (0,080), appraisal support (0,641), and instrumental support (0,698) greater than alpha (0,05) so that Ho failed to be rejected. Some things that are suspected of influencing the lack of differences in social support include ease of accessing health information, there was motivation from health workers, lack of praises from family, and accessibility of elderly’s posbindu. There was no relation between social support with elderly’s posbindu utilization.